Chemical Safety Knowledge Assessment of Academic Researchers from Brazil during Covid-19 Pandemic - Pedreira Filho, Walter dos Reis; Passos, Julia Sapienza; Ruscic, Nadia; da Silva, Maria Luiza da Silva; Monteiro, Lucilena Rebelo; Costa, Soraia Katia Pereira (International Journal of Occupational Safety and Health, 2023)
Introduction: Laboratories are inextricably dangerous work environments, as fatal incidents are reported in both academic and non-academic environments worldwide, where poor safety culture has been recognized as the major accident contributor. Workers can be exposed to chemical, biological, physical, or radioactive hazards, in addition to musculoskeletal stresses. In Brazil, hundreds of thousands of workers are employed in laboratories, either in private or public institutions. Although laboratory safety can be governed by local, state, or federal regulations, learning how to identify common laboratory hazards is the first step to preventing accidents in the lab environment.Methods: The study aimed to assess the degree level of safety culture in an academic population of research laboratories, located in the largest city in Brazil, and their compliance with occupational safety regulations during the COVID-19 outbreak. This study was carried out between October and November 2020. The results were obtained from the standardized questionnaire used to assess 98 researchers working in laboratories during the COVID-19 pandemic.Results: The majority of respondents (95%) reported being exposed to more than two risks, simultaneously.  About two-thirds (66%) of them were not fully aware of the laboratory's risk map. About half of the researchers (50%) were lacking in safety culture, and 57%and 43% were preoccupied with chemical and non-chemical hazards, respectively. Personal protective equipment (PPE) during laboratory work was used by most researchers, but 75% of researchers claim that security awareness learning should be a high priority for admission to laboratories. About 39% of researchers agreed that awareness of security must be improved in their laboratoriesConclusion: The survey proves the lack of information and attitudes about chemical safety, especially among less experienced researchers, even if they use personal protective equipment when necessary.